Characterization of patient´s falls in a cardiology hospital - Silmara Meneguin; Jairo Aparecido Ayres; Giovana Hass Bueno (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769213554 Objective: To characterize patient falls, according to records of adverse events, in wards of a cardiology hospital in the city of São Paulo. Method: retrospective study in which a descriptive analysis was carried out with 67 reports of adverse events occurred in the first semester of 2007. Results: 2.04 falls/ 1.000 patients-day were reported. Most patients were male (59.7%), at mean age of 64.04 years old. The falls occurred in the first 30 days of hospitalization (58.2%) at night (55.2%). Concerning the places where the falls occurred, the bedroom and the bathroom showed the highest prevalence, 73.1% and 22.4%, respectively. Falls from one's own height contributed with  64.2% of the cases, from armchairs 18.0%, and from bed 10.4%.  Conclusions: the results of the present study point out the need for more care with elderly patients, at night, in the bedroom and especially during the first thirty days of stay.